SOCIO-PRAGMATIC STUDY; THE OBSCURITY OF GRICEAN MAXIMS (COOPERATIVE PRINCIPLE RULES) [The Study of Flouted Maxims in Conversation through Gender Categories] - Rohaniyah, Jaftiyatur (OKARA: Jurnal Bahasa dan Sastra, 2013)
Flouting maxims was a kind of violation on cooperative principles which consist of four maxims. In this case, cooperative principles were cooperation between speaker and hearer to make successful communication. In doing conversation, it was suggested to make the contribution as informative as is required and do not make the contribution more informative than required, do not say what believed to be false, make the contribution relevant and avoid obscurity and ambiguity. These all must be obeyed in doing conversation in order to make a successful communication according to Grice. If it is violated by speaker, it is called by flouting the maxims. The speaker in this case has the intention to arise his implicature. It often used in classroom interaction when teacher and students doing conversation especially in speaking class. It was almost done by students in answering the teacher’s question, where the students was not male students only, but also female students are on that part. Theoretically, female identified as a talkative person more than man. It means that female has ability to show her emotion by producing too much word in conversation which was able to arise implicature. This part can effect to the cooperative principles to make successful communication. Thus, it was true that gender hold the important rule in pragmatic study.